2017
DOI: 10.5812/pedinfect.57276
|View full text |Cite
|
Sign up to set email alerts
|

Role of Vitamin D [25(OH) D] Deficiency in Development of Pneumonia in Children

Abstract: Background: Pneumonia is a leading cause of children's morbidity and mortality worldwide. Some studies have reported that vitamin D deficiency is associated with an increased incidence of lower respiratory illness requiring hospitalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 13 publications
2
24
0
2
Order By: Relevance
“…In our study, 92% and 80% of patients with complicated and uncomplicated pneumonia, respectively, had poor vitamin D status. This is in line with previous reports that confirmed the association between inadequate vitamin D levels and increased risk for CAP [ 35 , 36 ]. Moreover, vitamin D deficient status was associated with an increased risk of complicated pneumonia by about 1.7 folds.…”
Section: Discussionsupporting
confidence: 94%
“…In our study, 92% and 80% of patients with complicated and uncomplicated pneumonia, respectively, had poor vitamin D status. This is in line with previous reports that confirmed the association between inadequate vitamin D levels and increased risk for CAP [ 35 , 36 ]. Moreover, vitamin D deficient status was associated with an increased risk of complicated pneumonia by about 1.7 folds.…”
Section: Discussionsupporting
confidence: 94%
“…Malnutrition, which continues to be a common problem in developing countries, exacerbates the symptoms of pneumonia, prolongs the disease duration, and increases mortality (4). In a previous study, we found a significant association between children's vitamin D serum levels and developing pneumonia (5). Through strengthening the immune system to defend against infections, zinc has an important role in preventing pneumonia (6).…”
Section: Introductionmentioning
confidence: 91%
“…Hashemian et al, [ 12 ] advocated providing children (particularly suffering from pneumonia) with adequate amounts of vitamin D supplements. Nevertheless, little research has been conducted to measure the impact of supplementation of vitamin D on the outcome of pneumonic children.…”
Section: Introductionmentioning
confidence: 99%